2020
DOI: 10.1021/acs.jpcb.0c04259
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Lattice Constant of A2XY6 Cubic Crystals Using Gene Expression Programming

Abstract: Lattice constant is one of the paramount parameters that mark the quality of thin film fabrication. Numerous research efforts have been made to calculate and measure lattice constant, including experimental and empirical approaches. Not withstanding these efforts, a reliable and simple-to-use model is still needed to predict accurately this vital parameter. In this study, gene expression programming (GEP) approach was implemented to establish trustworthy model for prediction of the lattice constant of A2XY6 (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Computational prediction of lattice constants of crystal materials has wide applications in both materials property prediction and discovery, 5 crystal structure prediction, 6 , 7 and large screening of materials for materials fabrication. 8 Lattice prediction models are very helpful for the crystal structure prediction algorithms, which can allow conducting mutagenesis experiments to examine how composition changes may affect the structural mutations in terms of lattice constant changes or symmetry breaking. Crystal structure prediction can also be used to augment the X-ray diffraction (XRD)-based crystal structure determination via space group identification or providing initial parameters for the XRD-based Rietveld refinement method for structure determination.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Computational prediction of lattice constants of crystal materials has wide applications in both materials property prediction and discovery, 5 crystal structure prediction, 6 , 7 and large screening of materials for materials fabrication. 8 Lattice prediction models are very helpful for the crystal structure prediction algorithms, which can allow conducting mutagenesis experiments to examine how composition changes may affect the structural mutations in terms of lattice constant changes or symmetry breaking. Crystal structure prediction can also be used to augment the X-ray diffraction (XRD)-based crystal structure determination via space group identification or providing initial parameters for the XRD-based Rietveld refinement method for structure determination.…”
Section: Introductionmentioning
confidence: 99%
“… 9 While the majority of methods are based on composition information, the structure-based approaches can also bring interesting insights. 8 In this paper, 9 a deep learning method is proposed to predict lattice parameters in cubic inorganic perovskites based on Hirshfeld surface representations of crystal structures. They showed that two-dimensional Hirshfeld surface fingerprints contain rich information encoding the relationships between chemical bonding and bond geometry characteristics of perovskites.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations